The Influence Of The Independent Learning-Based Education Unit Curriculum On Teacher Performance - Tri Maulina, Amey; Afni, Nur; Ashari Hamzah, Rahma (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to determine how the effect of the independent learning-based education unit curriculum on teacher performance at SD Negeri Maradekaya I Makassar City. This type of research is survey research using quantitative research methods. The population of this study were all 12 teachers of SD Negeri Maradekaya I Makassar City. The samples of this study were principals, class teachers and subject teachers totaling 10 people where 1 male teacher and 9 female teachers. The instruments used were observation sheets, questionnaires and documentation. Data analysis techniques used are descriptive analysis and inferential analysis. The results showed that: 1) An overview of the curriculum of education units based on independent learning, this is realized by the curriculum of education units based on independent learning prioritizing student-centered learning, focusing on critical thinking processes, problem solving and project-based learning. The adjustment of the education unit curriculum based on independent learning is able to create a more inclusive and adaptive learning environment, where teachers can adjust teaching methods to suit the potential and abilities of students. 2) Teachers' performance is highly influential on the quality of the learning process and students' overall development; teachers must also have the ability to build positive interactions with students and create a conducive classroom atmosphere. 3) The independent learning-based education unit curriculum affects teacher performance at SD Negeri Maradekaya I Makassar City after the results of hypothesis testing with a significance value of 0.000 <0.05 mean that there is an effect of the independent learning-based education unit curriculum on teacher performance.